0408 A Blinded Hypnotic Tapering Approach for Hypnotic discontinuation. (12th April 2019) - Edinger, Jack D; Wamboldt, Frederick; Holm, Kristen; Johnson, Rachel L; Simmons, Bryan; Tsai, Sheila; Morin, Charles M
Abstract: Introduction: Hypnotic users commonly make unsuccessful attempts to discontinue their hypnotics. This study tested a blinded tapering approach to reduce anxiety and help patients discontinue their hypnotics. Methods: This study enrolled 78 (M age = 55.2 ± 12.8 yrs.; 65.4% women) users of benzodiazepine and benzodiazepine receptor agonists. Enrollees completed baseline measures including the Insomnia Severity Index (ISI). They then completed 4 sessions of cognitive behavioral insomnia therapy (CBTI). Subsequently they were randomized to one of three 20-week, double-blinded tapering protocols wherein their medication dosage was either reduced by 25% or 10% every two weeks, or remained unchanged (CTRL). During tapering, all enrollees were seen biweekly by the study physician for support and guidance. At the end of the 20-week period the study blind was eliminated and those who completed one of the two blinded tapering protocols entered a 3-month follow-up period, whereas CTRL participants are offered an open label taper before completing the follow-up. Results: Baseline ISI scores (ISI=18.07±0.58) showed that the total sample entered the trial with moderately severe insomnia complaints despite almost nightly hypnotic use. These scores declined into the mild range after CBTI (10.19±0.53) and tapering (9.62±.63) and approached the normative range by follow-up (7.59±1.05). Of the 45 who completed one of the blinded tapering protocols to date, 39 (86.7%) totally discontinued their medication use by the end of the 20-week tapering phase whereas 12 (75%) of 16 in the CTRL group discontinued hypnotic use by the end of their open label tapering. At follow-up 22 of 30 (73.3%) who completed blinded tapering remained medication free whereas only 5 of 14 (35.7%) in the CTRL group who underwent open-label tapering remained medication free. Conclusion: CBTI combined with blinded hypnotic tapering seems a promising treatment approach to help hypnotic users overcome their medication dependence and improve insomnia symptoms. Support (If Any): National Institute of Drug Abuse, Grant # R34 DA042329-01